N-[2-(4-Methylbenzoyl)ethyl]propan-2-aminium chloride - Sahin, Ertan; Akkurt, M.; Gul, Halise İnci; Mete, Ebru; Aydın, A. (International Union of Crystallography (IUCr), 2012)
In the title compound, C(13)H(20)NO(+)·Cl(-), the protonated amino N atom is hydrogen bonded to the chloride anion. N-H⋯Cl hydrogen bonds link the anions and cations into dimers, which are connected by C-H⋯O hydrogen bonds, forming supra-molecular chains extending along [100].
Keywords: Crystallography; QD901-999; Organic Papers; 3. Good health